The Effects of Post-Election Protests on the Rule of Law and Democracy: A Study of Tanzania after the 2025 General Election - Ruhangisa, Valentine Flavian (Jurnal Transformative, 2026)
The 2025 general elections in Tanzania were a pivotal moment in the nation's political history, leading to significant protests within its democratic and legal framework that highlighted deepening divisions in Tanzania's democratic and legal system. This article critically addresses the implications of these protests following the elections, in terms of democratic institutions, legal frameworks, and civil liberties in Tanzania. Based on a systemic analysis of news reports, human rights testimonies, and academic sources, the paper highlights the lack of constitutionalism, the weaponized application of legal norms, and coercive state actions such as mass arrests, internet shutdowns, and assembly restrictions. The novelty of this study lies in filling a critical conceptual gap in hybrid regime literature; while existing scholarship heavily concentrates on conventional electoral management or media limitations, this paper shifts the focus toward the unexamined legal consequences of post-election state repression and its direct impact on legal consciousness, specifically capturing how a new generation of social-media-coordinated citizen mobilization interacts with state-level autocratic legalism. The Tanzanian government's actions are shown to consolidate executive power while systematically undermining institutional checks and balances situated between competitive authoritarianism and democratic backsliding. The profound implications of these findings reveal that the state's reliance on 'rule-by-law' and total judicial deference to the executive severely jeopardize horizontal accountability, cultivating a pervasive atmosphere of fear that systematically withdraws citizens from the deliberative political arena, while the increasing militarization of civilian spaces ultimately sacrifices long-term democratic legitimacy for temporary, coercive stability . The paper concludes with strategic structural recommendations, including eliminating political interference in judicial appointments and independent restructurings of the national electoral commission to restore a democratic social contract.